(untitled) (Filološke studije, 2019)
We are living or we used to live in times of globalization, but not many of us know how to define its effects on the kind of communication we all comprehend. Being a new type of media, computers have partially replaced the kind of communication we were familiar with untill the television as a media was born, but it has also replaced the television itself, leading to the fact that computer technology brings about media revolution. Internet transforms the way we communicate and those changes, furthermore, affect us. Important notion regarding Internet culture is that it is a culture of the creator of the Internet, and it is a system of values and beliefs that form our behaviour. The way in which literature exists on the Internet and how its consumers communicate with one another we observed on the example of Max Dizdar - his character and work on the Internet. Literature on the Internet is usually presented through 4-part system, including: Wikipedia (Internet encyclopedia), forum, blog and the official sites. The other forms of re-presentation can or do not have to be present, depending on the fact how interesting the sites are and how many visits per site there are. Representation of Mak Dizdar in all those forms of Internet communication have shown that the Internet communication abstracts the space and time and it circles in waves through virtual spaces, making the consumers a display in which millions of light impulses circle in their homes. Based on the results, it can be noted that the new system of communication is supported by networked integration which is the basic characteristics of its activation and inclusion of all cultural expressions. Therefore, the only important thing for the user becomes the message itself and the past, the presence and the future can be programmed to merge into mutual communication within one single message.